Investigation of Association with First-Trimester Free Human Chorionic Gonadotropin-ß, Pregnancy - Associated Plasma Protein-A, and Adverse Pregnancy Outcomes - Gokhan Gonen; Yasam Kemal Akpak; Murat Muhcu (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: This study aimed to investigate the association between first-trimester screening maternal serum markers (free human chorionic gonadotropin-beta (β-hCG), pregnancy-associated plasma protein-A, and adverse pregnancy outcomes (gestational hypertension, preeclampsia, preterm delivery, intrauterine growth restriction, oligohydramnios, intrauterine ex-fetus, abruptio placentae, and gestational diabetes mellitus).